Back to Global Imbalances? - de la Torre, Augusto; Schmukler, Sergio L.; Servén, Luis (World Bank, Washington, DC, 2012)
The 2008-2009 financial crisis has shaken the prevailing equilibrium of the global economy, with a collapse in capital flows and international trade. How will the post-crisis constellation of current account imbalances look? Will the world resume financing the United States (US), and continue sustaining large external imbalances there? Contrary to what many expected, some forces unleashed by the crisis have kept US assets attractive and the dollar strong, decreasing the need for an immediate reduction of global imbalances. Over the long run, however, real sector and financial sector forces are likely to impose a correction, perhaps involving a depreciation of the dollar and a major reallocation of international portfolios.